2021
DOI: 10.1088/1755-1315/842/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Local visitors’ willingness to pay of entrance fee at Taman Negeri Gunung Stong, Kelantan

Abstract: The forest ecosystem offers plenty of benefits and provisions for the environment and human wellbeing. One of the forest ecosystem’s potential advantages is that it serves as a recreational forest area for tourists. However, most tourist destination faces minimal or raising public support for natural attraction maintenance and management. Hence, managing the recreational forest lacks financial resources to provide and restore adequate recreation facilities. This study aims to determine local visitors’ willingn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…They specify why they do not believe the payment will be used for nature conservation, and one considers that it is not his responsibility to pay that entrance fee, as presented in Table 4. A similar study from [7] & [9] showed that respondents are reluctant to pay since they did not understand the value of protecting the natural environment for living and non -living organism's survival. Reason not willing to pay a.…”
Section: Willingness To Pay (Wtp)mentioning
confidence: 99%
See 1 more Smart Citation
“…They specify why they do not believe the payment will be used for nature conservation, and one considers that it is not his responsibility to pay that entrance fee, as presented in Table 4. A similar study from [7] & [9] showed that respondents are reluctant to pay since they did not understand the value of protecting the natural environment for living and non -living organism's survival. Reason not willing to pay a.…”
Section: Willingness To Pay (Wtp)mentioning
confidence: 99%
“…Third phase: from 1990 to the present, when the region underwent ecotourism development and launched the inaugural Visit Malaysia Year campaign. [7]. In Malaysia, Kelantan is renowned as a state with several natural environmental landmarks and a rich cultural history that supports the sector's development and boosts local income.…”
Section: Introductionmentioning
confidence: 99%